1998
DOI: 10.1111/j.1540-4560.1998.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Thriving

Abstract: These scales are designed to assess perceived bene$ts that result from a spec@ stressox Research with the SRGS suggests a unidimensional structure of thriving, whereas research with the PTGI suggests a multidimensional structure. Two possible reasons for this inconsistentfinding concern diflerences in the method ofparticipant selection and in the recall period for the reporting of stressful events. In addition, we present a number of strategies to validate self-report measures of thriving, including corroborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Even though various scholars (e.g., Cohen et al, 1998;Taku et al, 2008) found that the PTGI should be considered as a multi-dimensional measurement, in our sample we obtained through PCA a one-factor PTG model including 17 items. The assumption that personal growth is a unitary phenomenon is not new as shown in scholarly literature (Joseph et al, 2004;Sheikh & Marotta, 2005).…”
Section: Quantitative Studymentioning
confidence: 99%
“…Even though various scholars (e.g., Cohen et al, 1998;Taku et al, 2008) found that the PTGI should be considered as a multi-dimensional measurement, in our sample we obtained through PCA a one-factor PTG model including 17 items. The assumption that personal growth is a unitary phenomenon is not new as shown in scholarly literature (Joseph et al, 2004;Sheikh & Marotta, 2005).…”
Section: Quantitative Studymentioning
confidence: 99%
“…First, the structural model's predictive power was assessed using the endogenous construct's coefficient of determination (R2 values) (Hair et al 2017;Henseler, Ringle, and Sinkovics 2009;Ringle, Da Silva, and Bido 2014). The R 2 values for safety attitude were 0.149, indicating a modest predictive potential, but the R 2 values for safety knowledge (0.232) and safety behaviour (0.361) were significant (Cohen et al 1998). On the other hand, the predictor constructs can be assessed by using the effect size of Cohen , f 2 (Glass and Cohen 2012).…”
Section: Structural Model Assessment (Hypothesis Testing)mentioning
confidence: 99%
“…The effect size (f 2 ) helps to assess if there is any significant effect from the omitted predictor construct on the value of R 2 for the endogenous construct. According to Cohen et al (1998)…”
Section: Discriminant Validity -Heterotrait-monotrait (Htmt) Criterionmentioning
confidence: 99%
“…Existing studies show that adjustment needs short term or long-term process for adjustment it will sometimes cause psychological stress (Aycan, 1997). Several researches also shows that stressful in mental will causing poor adjustment and job dissatisfaction (Cohen, Cimbolic, Armeli, & Hettler 1998). In contrast, expatriates who are well-adjusted can lead to good mental health and life satisfaction with positive relationships with local people, compatibility with jobs, and a positive attitude toward new characteristics of jobs.…”
mentioning
confidence: 99%